Y'all don't (really) care about black women [compact disc] - Charles, Melanie (Impulse, 2021)
Melanie Charles sets out to take this group of songs and breathe new energy into them. Melanie was immediately drawn to the rapturous voices of Billie Holiday and Sarah Vaughn who inspired her to record arrangements of God Bless the Child and Detour Ahead. This album is a love letter to the unheralded labor of black women. Melanie asks listeners to be accountable to black women as much as they care for their works.